Chondrocyte Viability at Time of Transplantation for Osteochondral Allografts Preserved by the Missouri Osteochondral Preservation System versus Standard Tissue Bank Protocol - Stoker, Aaron M.; Stannard, James P.; Cook, James L. (The Journal of Knee Surgery, 2018)
The Missouri Osteochondral Preservation System (MOPS) has been reported to effectively preserve osteochondral allografts (OCAs) twice as long as current tissue bank protocols in preclinical studies. However, viability of OCAs preserved using the MOPS protocol at the time of clinical implantation compared with the current standard of care (SOC) is not known. Viable chondrocyte density (VCD) at time of transplantation will be significantly higher in OCAs preserved using the MOPS protocol compared with OCAs preserved using the current tissue bank protocol and will significantly affect clinical complication rates. Femoral condyle OCAs were obtained from American Association of Tissue Banks accredited tissue banks for clinical use. The OCAs were stored using the current SOC protocol for each respective tissue bank (n = 26) or the MOPS protocol (n = 50). Nonimplanted femoral condyle OCA tissue normally discarded after surgery was collected and assessed for VCD within 1 hour after surgery. Control OCA samples (n = 34) were obtained from one tissue bank. VCD was determined using a validated cell viability assay. Patients (n = 76) had in-clinic follow-up at least 6 months after OCA transplantation. At the time of clinical implantation, mean storage time for OCAs in the SOC cohort was 20.4 days, and in the MOPS cohort was 44.2 days, after procurement. VCD in OCAs in the MOPS cohort was not significantly different from normal healthy cartilage VCD and 100% were above the desired minimum essential level 70% of control VCD at the time of transplantation. VCD in OCAs in the SOC cohort was significantly (p < 0.001) lower than controls and MOPS, and only 27% were above 70% of control VCD at the time of transplantation. MOPS preserves OCA chondrocyte viability at significantly higher levels than current tissue bank storage protocols for a longer period of time after procurement. All MOPS-preserved OCAs exceeded minimum essential VCD levels for up to 56 days after procurement.
Keywords: osteoarthritis; osteochondral allografts; preservation systems; chondrocyte viability; cartilage